Primum non nocere – Are chloroquine and hydroxychloroquine safe prophylactic/treatment options for SARS-CoV-2 (covid-19)? - Biguetti, Claudia; Mauro Toledo Marrelli,; Marco Broto, (Revista de Saúde Pública, 2020)
ABSTRACT Chloroquine (CQ) and its analog hydroxychloroquine (HCQ) were recently included in several clinical trials as potential prophylactic and therapeutic options for SARS-CoV-2 infection/covid-19. However, drug effectiveness in preventing, treating, or slowing the progression of the disease is still unknown. Despite some initial promising in vitro results, rigorous pre-clinical animal studies and randomized clinical trials have not been performed yet. On the other hand, while the potential effectiveness of CQ/HCQ is, at best, hypothetical, their side effects are factual and most worrisome, particularly when considering vulnerable groups of patients being treated with these drugs. In this comment, we briefly explain the possible mechanisms of action of CQ/HCQ for treating other diseases, possible actions against covid-19, and their potent side effects, in order to reinforce the necessity of evaluating the benefit-risk balance when widely prescribing these drugs for SARS-CoV-2 infection/covid-19. We conclude by strongly recommending against their indiscriminate use. DESCRIPTORS: Coronavirus Infections. Chloroquine, toxicity. Hydroxychloroquine, toxicity. Contraindications, Drug.